The Analysis Pedagogical Practice and Transformations to ICT on Learning and Achievement of the Certified English Teacher at SMPN 28 Selayar - Ahdiani Ahdiani; Ummi Khaerati Syam; Hilda Hafid (FKIP Unismuh Makassar, 2019)
This study's objective was to analyze pedagogic practices and changes in ICT in the learning and achievement of certified English teachers at SMPN 28 Selayar. This study uses qualitative research with a descriptive approach, using data collection techniques of observation, interviews, and documentation studies.Based on the findings, it was determined that pedagogical practices and ICT changes in English learning were very good. This was demonstrated by the enthusiastic English teachers who always encourage students to participate more actively in the teaching and learning process so that the potential that each student possesses can grow. The teacher's learning activities include applying various teaching techniques outside of the classroom in addition to listening to students learn in the classroom. Students prefer group discussions and question-and-answer sessions, which are of course supported by learning tools like LCD projectors, radios, laptops, and other devices that can support learning. As a result, students are highly motivated to participate in lessons and other educational activities.